Assessment of Hand Function during the Period of Three Months after Surgical Intervention for Unstable Metacarpal and Phalangeal Fractures: A Comparison between Wide Awake Local Anesthesia No Tourniquet (WALANT) Versus Bier’s Block - Kastanis G; Siligardou MK; Chaniotakis C; Tsioupros A; Pantouvaki A; Kapsetakis P; Stavrakakis I (Medical Science: Trends and Innovations Vol. 8, 2025)
Background: Hand fractures are a common injury in the emergency department, and the majority of these are stable injuries that can be treated conservatively with excellent functional results. When respective injuries are characterized as unstable, surgical reduction and stabilization are necessary. The main purpose of surgical treatment of unstable hand fractures (metacarpal-phalangeal) is early mobilization to enhance hand functionality and to avoid stiffness functional incompetence. Generally, these operations are conducted under regional or general anesthesia to avoid pain and tourniquet for bloodless surgical fields. Wide Awake local anesthesia no tourniquet (WALANT) procedure is described as local injection of anesthetic agent and epinephrine without tourniquet application, with scope to allow local anesthesia without other sedation and at the same time hemostasis. Aim: The purpose of the study is to compare the functional assessment of the hand function during a period of three months after surgical intervention for unstable metacarpal and phalangeal fractures under WALANT versus Biers block. Materials and Methods: Between May 2021 to October 2022, 43 patients with unstable metacarpal and phalangeal fractures underwent open reduction and internal fixation, 21 cases with Biers block (BB) anesthesia and the rest with WALANT technique. Metacarpal fractures appeared in 29 cases and phalangeal fractures in 14 patients. Patients were operated on within the first week of the injury. According to implants they employed locking plates, screws and Kirschner wires in two groups. In both groups, examination with a C-arm intensifier was performed to check the final osteosynthesis and screw sizes. A standard rehabilitation protocol program from the first postoperative day was applied in all patients starting from adjacent joints. Patients were trained to follow a personalized home-based daily exercise program to increase the range of movement and enhance muscle strength and grip strength in a later phase. The mean quick DASH score and a Likert type of scale regarding satisfaction, three months after the operation were measured. Results: At three months postoperatively, Quick Dash Score is better in the WALANT group while patients’ satisfaction does not differ between the two groups. In the WALANT group, the immediate postoperative median VA Score appeared 2/10, while in the Biers block group appeared to be 6/10. Patients who underwent the WALANT technique were discharged on the same day after the operation, while the patients with regional anesthesia were the next postoperative day. The mean duration of analgesic use was shorter in the WALANT group (2,3 days) than in the BB group (5,7 days). Conclusion: Unstable metacarpal or phalangeal fractures are common injuries with the main treatment to be open or close reduction and internal fixations with locking plate or Kirshner wires. Objective of surgical treatment of unstable hand fractures (metacarpal-phalangeal) is early mobilization and enhanced hand functionality to avoid stiffness and tendon adhesions. Wide Awake Local Anesthesia No Tourniquet technique is an alternative sedative procedure which immediately offers postoperative numerous advantages (low-cost technique, no complication from tourniquet, decreased sensation of intra or postoperative pain) compared with Bier’s block anesthesia. Based on our results, it was concluded that the WALANT technique offers many benefits in the surgical treatment of hand fractures and is suggested as the first-choice anesthesiologist procedure.